2016
DOI: 10.1161/strokeaha.116.014578
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Therapy Reduces the First Stroke Risk Associated With Hypercholesterolemia Among Hypertensive Patients

Abstract: Background and Purpose-We sought to determine whether folic acid supplementation can independently reduce the risk of first stroke associated with elevated total cholesterol levels in a subanalysis using data from the CSPPT (China Stroke Primary Prevention Trial), a double-blind, randomized controlled trial. Methods-A total of 20 702 hypertensive adults without a history of major cardiovascular disease were randomly assigned to a double-blind daily treatment of an enalapril 10-mg and a folic acid 0.8-mg tablet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Among participants with LDL-C above 2 mmol/L, the benefit of folic acid was greater: a 31% reduction in stroke 47 . Importantly, folic acid was beneficial in participants with impaired renal function 48 .…”
Section: Nutritionmentioning
confidence: 97%
“…Among participants with LDL-C above 2 mmol/L, the benefit of folic acid was greater: a 31% reduction in stroke 47 . Importantly, folic acid was beneficial in participants with impaired renal function 48 .…”
Section: Nutritionmentioning
confidence: 97%
“…Recently, our China Stroke Primary Prevention Trial (CSPPT) subgroup analysis [3] found that, for participants not receiving folic acid treatment, high total cholesterol (TC) (≥ 200 mg/dL) was an independent predictor of first stroke when compared with low TC. Folic acid supplementation for 4.5 years significantly reduced the risk of first stroke by 31% among hypertensive participants with high TC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of B vitamins and folic acid as secondary prevention in patients with vascular diseases was not supported. However, in the primary prevention clinical trials, folic acid supplementation significantly reduced the risk of first stroke (Huo et al., ; Qin et al., ). Why is lowering HCY useful in primary prevention and useless in secondary prevention?…”
Section: Discussionmentioning
confidence: 99%